2018
DOI: 10.3329/dujps.v16i2.35262
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Antibiotic Sensitivity Profile of Bacteria Isolated from Patients with Respiratory Tract Infections in Bangladesh

Abstract: ABSTRACT:The study was aimed to characterize bacterial isolates from respiratory tract infections (RTI) and investigate their antibiotic sensitivity profile. Selective media and biochemical tests were used to characterize 40 bacterial isolates. Antibiotic sensitivity testing was conducted using Kirby-Bauer disc diffusion method. About 42.5% (17) RTI patients were infected by Klebsiella pneumoniae, 30% (12) by Escherichia coli and 27.5% (11) by Pseudomonas aeruginosa with no significant gender variation (p-valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Further, the present study observed that Klebsiella spp. was the predominant bacterial isolate from the respiratory samples and similar observations were documented from the different healthcare settings of the world [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 60%
“…Further, the present study observed that Klebsiella spp. was the predominant bacterial isolate from the respiratory samples and similar observations were documented from the different healthcare settings of the world [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 60%
“…Klebsiella was also found as predominant organism in studies done by Ahmed et al, Promite et al and Manikandan et al showing 59.7%, 42.5% and 28.4% frequency respectively. [5][6][7] In this study, the other common isolated pathogens were Acinetobacter (13.49%) and Pseudomonas (13.23%). This finding correlates with the findings of Ali et al 8 showing prevalence of Acinetobacter and Pseudomonas to be 13.69% and 35.35% respectively.…”
Section: Discussionmentioning
confidence: 88%
“…Amikacin and gentamycin were found to be sensitive to Klebsiella in other studies. 6,10 Acinetobacter was sensitive to many antibiotics e.g., imipenem, piperacillin/tazobactam, cefuroxime etc. but the association was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiella was the predominant microorganism isolated from these samples (45.2%). Klebsiella was also found as a predominant organism in studies done by [12][13][14][15] Another previous study which was conducted in the same institution two years before also reported that Klebsiella was the most commonly isolated organism from the sputum samples of hospitalized patients with community-acquired pneumonia. 16 In this study, the other common isolated pathogens were Pseudomonas (17.3%) and Acinetobacter (14.4%).…”
Section: Discussionmentioning
confidence: 99%